Training e-competent managerial teams and fostering the use of new technology at the university - Estévez Arias, M. Sc. Orosmán Vladimir; Sánchez CervantesI, M. Sc. Mislene María (Transformación, 2024)
The research aims at assessing a strategy devised to enhance "e-competent" team managers’ training for introducing virtual learning environments techniques into the process of professional education at the faculties of Sports and Agricultural Sciences at the University of Camagüey. The use of empirical methods reveals managers and professors’ viewpoints on ICT-supported learning strategies, together with a study of the state of the art. The devised strategy includes three stage and five areas (technological, pedagogical, organizational, teacher developmental and student developmental). The strategy yields positive outcomes at the Faculty of Sport but fails at the other faculty. This paper describes such outcomes in each faculty. The study confirms that the successful outcomes of ICT-supported learning are directly related to team managers’ pedagogical, organizational, and technological competence. Likewise, the university staff pedagogical, technological, and organizational shortcomings in integrating ICT into the substantive process might significantly be reduced by developing managers’ pedagogical, organizational and technological leadership.